IMPLEMENTATION OF ANDROID-BASED INTERACTIVE MULTIMEDIA ON ATOM STRUCTURE MATERIALS ON LEARNING OUTCOMES AND STUDENT MOTIVATION - Yudha, Sandy; Nurfajriani, Nurfajriani; Silaban, Ramlan (Universitas Tanjungpura, 2023)
The purpose of this study was to determine the effect of implementing Android-based interactive multimedia on learning outcomes and student motivation at SMA Negeri 1 Binjai, Langkat Regency. The method used in this research is the descriptive quantitative research method. The data collection instruments used in this study were questionnaires (questionnaires) and tests. The data analysis technique used in this research is a quantitative descriptive analysis using the one-sample t-test formula and correlation test. The learning outcomes of students who are taught using Android-based interactive multimedia obtained by students are higher than the KKM value set at school, which is 75, with an average value of student learning outcomes of 86.91 and a sig. = 0.000 0.05 from the results of the one-sample t-test conducted. The results of the student's motivation towards android-based interactive multimedia obtained an average percentage of 87.57 in the highly motivated category. Motivation and learning outcomes of students have a positive relationship with a very strong strength with the obtained Pearson Correlation value of 0.941 and a coefficient of determination of 88.5%.